If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 17r + -2 = 5r + 90 + -2r Reorder the terms: 8 + -2 + 17r = 5r + 90 + -2r Combine like terms: 8 + -2 = 6 6 + 17r = 5r + 90 + -2r Reorder the terms: 6 + 17r = 90 + 5r + -2r Combine like terms: 5r + -2r = 3r 6 + 17r = 90 + 3r Solving 6 + 17r = 90 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 6 + 17r + -3r = 90 + 3r + -3r Combine like terms: 17r + -3r = 14r 6 + 14r = 90 + 3r + -3r Combine like terms: 3r + -3r = 0 6 + 14r = 90 + 0 6 + 14r = 90 Add '-6' to each side of the equation. 6 + -6 + 14r = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 14r = 90 + -6 14r = 90 + -6 Combine like terms: 90 + -6 = 84 14r = 84 Divide each side by '14'. r = 6 Simplifying r = 6
| 0.34*2= | | 16*30= | | -2(12a-1)+9(-8+12a)=-70 | | 2x+6=4x+7 | | n/-6=-50 | | -8=32-q | | 1.01/3 | | (2x+7)3=-9 | | 3(y-2)+8y=-39 | | 12-2x=-2(y-x) | | .8p-4=.33p | | P-(-5)=-6 | | -8x+6x= | | n^2+4n-7=0 | | 3x+2y=168 | | 4(u+3)+8u=-24 | | 16*60= | | 8b-2=-7(4-2b)+2 | | 2+8x=-70 | | 2(y+3)=11-3y | | 4.1=-15.1+6v | | y^2+y+.25=0 | | -(5b+6)=-7b | | 6(.60+x)=7x | | -(5x-3)=7(3x+5) | | 7(w-5)-4w=-8 | | 3=0.5(12)/v | | 22r+60=16 | | 9(1-5n)=-45n-34 | | 20x-(-8)-6x=10x+20 | | 7(z-1)-(3+8z)=-2z | | -2x+6(x+4)=-16 |